A biomimetic host from a poultry bone structure enables dendrite‐free lithium deposition - Feiyang Yang; Feng Wu; Zhaolin Gou; Lijun Zheng; Junce Wang; Ziyi Chen; Cunzhong Zhang; Yuefeng Su; Jun Lu; Ying Yao (Carbon Energy)
Abstract Lithium metal anode is one of the ideal anode materials for the next generation of high‐energy‐density battery systems. Unfortunately, the uneven nucleation of Li leads to dendrite growth and volume changes during cycling, resulting in poor electrochemical performance and potential safety hazards, which hinder its practical application. In this work, a low‐cost chicken‐bone‐derived carbon material (CBC) with a biomimetic structure was designed and synthesized using a simple one‐step carbonization method. Combining theoretical calculations and experimental results, the self‐doped N and S heteroatoms in CBC are demonstrated to effectively reduce the binding energy with Li atoms and lower the nucleation overpotential. After uniform nucleation, the Li metal grows in a spherical shape without dendrites, which is related to the reduction of the local current density inside the biomimetic crosslinking structure of CBC. Benefiting from this favorable Li growth behavior, the Li@CBC electrode achieves ultra‐low nucleation overpotential (15.5 mV at 0.1 mA cm−2) and superdense lithium deposition (zero volume expansion rate at a capacity of 2 mAh cm−2) without introducing additional lithiophilic sites. The CBC retains a high Coulombic efficiency of over 98% in 479 cycles (1 mA cm−2 and 1 mAh cm−2) when applied in a half‐cell with Li, and shows an excellent rate and cycling performance when applied in a full cell with LiFePO4 as the cathode.